State bodies regulating Russian-Asian trade in the first half of the XIX century (Revista de Investigaciones Universidad del Quindío, 2022)
The urgency of the investigated problem is caused by the state regulation of foreign economic relations is one of the priority political tasks. In the first half of the XIX century, when the era of colonial world division ended, the spheres of influence and colonial expansion of the world powers were outlined. During this period, rivalry with England in Central Asia, Iran and Transcaucasia proved strategically important to Russia. These territories had long been economic partners for Russia. The paper aims to show the role of specially created bodies in the Russian Empire in regulating trade and economic relations of the state with the countries of Central Asia, using general scientific and special-historical methods. The leading methods in the presented study are the method of institutional analysis, problem analysis, and comparative-historical method. Results show that In 1819, the Asia Department and the Asia Committee were established within the Ministry of Foreign Affairs due to reorganizations and the search for the best solution to the urgent problems of economic cooperation with Asian countries. A main task of regulating economic relations was customs and tariff regulation. The compilation and enactment of the Asian Tariff was central to the activities of the bodies that controlled Russian-Asian trade.
Keywords: foreign trade; Russo-Asian trade; state policy; government agency; Asia Department